Effect of Micro-Teaching Method Supported by E-Learning Platforms in Enriching Pre-service Mathematics Teachers' Teaching Practice s and Improve Self-efficacy - Marwa El-ahwal (International Journal of Instructional Technology and Educational Studies)
The objective of the current research is Effect of “Micro-Teaching “Method Supported by E-Learning Platforms in Enriching Pre-Service Mathematics Teachers' “Teaching practice “s and Improving Self-efficacy, and the research sample consisted of (60) students from the second year students, who were divided into two groups, Designing research tools (a note card for “Teaching practice “s) ,and a scale (for self-efficacy), and the researcher found that there are differences between the performance of students members of the experimental group in the note card of “Teaching practice “s in favor post application, as well as the existence of differences between the performance of students members of the “experimental and control group” in the practice note card Teaching in favor of the post application of the experimental group, which outperformed the control group, and the results also found differences between the performance of students, members of the “experimental and control group”, in the measure of self-efficacy in favor of the post application of the experimental group, which outperformed the control group.